Influence of Perceived Usefulness on Using the Shopee Application: Study on College Students - Azlyna, Via Nur; Nugraha, Jaka (Universitas Negeri Surabaya, 2023)
This research was conducted to know the effect of perceived usefulness on attitude, in the shopee application using the TAM (Technology Acceptance Model). This research was conducted at the Faculty of Economics and Business, Surabaya State University with the type of research used, namely quantitative with an explanatory research approach. The samples used in this study were from the Office Admistrasion Education student class of 2019, Economics Education student class of 2019, Commerce Education 2019, and Accounting Education 2019 with a total of 218 student. The data collection technique uses a questionnaire distributed via google form, besides that the data analysis technique in this study uses variant-based Structural Equation Modeling (SEM), namely by using the Generalized Structured Component Analysis (GSCA) method.